How is the Trade-off between Adverse Selection and Discrimination Risk Affected by Genetic Testing? Theory and Experiment - David Bardey; Philippe De Donder; César Mantilla (Center for Economic Studies and ifo Institute (CESifo), 2017)
We compare two genetic testing regulations, Disclosure Duty (DD) and Consent Law (CL), in an environment where individuals choose to take a genetic test or not. DD forces agents to reveal the test results to their insurers, resulting in a discrimination risk. CL allows agents to withhold that information, generating adverse selection. We complement our model with an experiment. We obtain that a larger fraction of agents test under CL than under DD, and that the proportion of individuals preferring CL to DD is non-monotone in the test cost when adverse selection is set endogenously at its steady state level.
Keywords: C91; D82; I18; 330; consent law; disclosure duty; personalized medicine; test take up rate; pooling health insurance contracts